Exercise or lie down? The impact of fitness app use on users' wellbeing - Cai, Jie; Li, Gang (Frontiers in Public Health, 2024)
The relationship between fitness app use and users' well-being and the influence mechanism was explored using structural equation modeling with upward social comparison as the mediating variable and self-control as the moderating variable. The questionnaire survey of 1452 fitness app users over 18 years old shows that: (1) fitness app use is associated with users' well-being; (2) upward social comparison plays a mediating role in the relationship between fitness app use and users' well-being; (3) self-control has a moderating effect on the relationship between fitness app use and users' well-being; upward social comparison can improve the well-being of high self-control users but reduce the well-being of low self-control users.